Association of the Gene FTO Single Nucleotide Polymorphism, rs9939609 with Type 2 Diabetes Mellitus in Pakistani Cohort - Afira Waqar; Bushra Chaudhry; Ikram-ul Haq; Ali Nawaz (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
To date, inconclusive data is available about the insight of the FTO gene variant with type 2 diabetes mellitus. T2DM is a chronic disease and a rising problem worldwide. Its complications lead to an increase in the burden of mortality specifically in lower and medium-income countries. Genome-wide association studies have spotted many genetic loci that are related to T2DM and validate the complicated polygenic traits. Many variants of different genes including FTO are associated with T2DM hence, this study was designed to inspect and unfold obscure data in South Asians. The main objective of present study is to identify the relation of FTO intronic variant rs9939609 with T2DM in Karachi-based Sindhi population of Pakistan. Total recruited individuals were grouped as diabetic cases and controls. Out of the total recruited subjects, genotyping was done on 152 samples using T-ARMS PCR however, demographic and clinical data were recorded of all individuals. The results showed that the frequency of variant genotypes in the diabetic case group was 11 % for AA, 45 % for AT and 44 % for TT though, the frequency of the lethal allele (T) was 34 %. These outcomes concluded, rare T allele frequency is higher among diabetic cases as compared to controls and provides the contribution from the Pakistani population to support the previous controversial findings. This study concluded FTO gene-single nucleotide polymorphism, rs9939609 is associated with T2DM but still, it is a growing need to do further studies on T2DM susceptible genes with different polymorphisms to recognize targets in the field of pharmacogenomics for clinical implementation.